2012
DOI: 10.1039/c2sm26072g
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of cured phenolic resins using complementary small-angle neutron and X-ray scattering and scanning electron microscopy

Abstract: The structure of cured phenolic resins prepared by compression molding of a deuterated phenolic resin oligomer and nondeuterated hexamethylenetetramine as a curing agent was investigated using complementary small-angle neutron scattering (SANS), small-angle X-ray scattering (SAXS), and scanning electron microscopy (SEM). Cured thermosetting resins have been considered to have an inherent inhomogeneity of the cross-links with sizes ranging from tens to hundreds of nanometers based on SEM observations of fractur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 52 publications
2
32
0
Order By: Relevance
“…When resins reach this final stage, they are often insoluble and exhibit relatively brittle properties at lower temperatures (T<T g ). [69,70] In our computational models, we track these structural transitions explicitly by identifying the first and second largest cluster sizes in the system and also by determining whether the largest cluster is percolating. The gel point can be identified as the point where the second largest cluster size drops rapidly, indicating the merger of two larger clusters into a single percolating cluster [20].…”
Section: Structural Analysismentioning
confidence: 99%
“…When resins reach this final stage, they are often insoluble and exhibit relatively brittle properties at lower temperatures (T<T g ). [69,70] In our computational models, we track these structural transitions explicitly by identifying the first and second largest cluster sizes in the system and also by determining whether the largest cluster is percolating. The gel point can be identified as the point where the second largest cluster size drops rapidly, indicating the merger of two larger clusters into a single percolating cluster [20].…”
Section: Structural Analysismentioning
confidence: 99%
“…We also carried out SAXS and SANS investigation on the structural inhomogeneity of insoluble phenolic networks near the gel point, and highly cured networks reacted with HMTA. [18][19][20] Our previous study of the gelation mechanism using SAXS demonstrated that the scattering function of phenolic resins in a tetrahydrofuran (THF) solution or fully THF-swollen states can be described by a combination of the Ornstein-Zernike and squared Lorentzian equations, which have correlation lengths of several nanometers. 19,20 The change in correlation length during the gelation process indicates the presence of two different gelation mechanisms that are dependent on the amount of cross-linker.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of voids was elucidated through complementary SAXS and SANS analyses. 18 Herein we report the evolution of NV clusters during the curing process in the pregel regime and the influence of an excess amount of HMTA on this evolution using DLS and gel permeation chromatography (GPC). An open two-roll mixing mill process was applied to control α by changing the number of roll-mixing times (N).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations